Happiness among Turkish and Moroccan immigrants in the Netherlands - (:unkn) unknown (Common Ground Research Networks, 2010)
This paper studies "happiness" among Turkish and Moroccan immigrants in the Netherlands in relation to social comparison and social identity. The statistics demonstrate that Moroccans, although they have lower income levels and higher unemployment rates than Turkish immigrants, are much more integrated to Dutch society and their happiness level is higher than the Turkish immigrants. In this paper we investigate the role of other factors than socio-economic factors like income, unemployment and education levels to explain the differences of happiness levels of Turkish and Moroccan Immigrants in the Netherlands. In order to examine this dilemma we use quantitative methods (by using World Database of Happiness), qualitative methods (by making interviews with the Moroccans and the Turks) and examine secondary sources on social and cultural aspects of the immigrants in the Netherlands. Our findings suggest that other than classic determinants of happiness some should consider how certain cultural facts, cultural integration and psychological processes (e.g. adaptation, aspirations, and comparisons) may increase happiness despite ostensible economic gains.*(* This research is supported by The Scientific and Technological Research Council of Turkey (TUBITAK) scholarship no. 2214.) © Common Ground, Ozge Gokdemir, Devrim Dumludag, All Rights Reserved.
Keywords: Behavioral economics; Happiness; Immigrants; Life satisfaction